2020
DOI: 10.1002/anie.201916712
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Rationally Designed Short Peptides Self‐Assemble and Bind Hemin to Promote Cyclopropanation

Abstract: The self‐assembly of short peptides gives rise to versatile nanoassemblies capable of promoting efficient catalysis. We have semi‐rationally designed a series of seven‐residue peptides that form hemin‐binding catalytic amyloids to facilitate enantioselective cyclopropanation with efficiencies that rival those of engineered hemin proteins. These results demonstrate that: 1) Catalytic amyloids can bind complex metallocofactors to promote practically important multisubstrate transformations. 2) Even essentially f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…Ac-K 4 (ChaKChaE) 2 -NH 2 Lysine residues 3C [153] Ac-K 2 (ChaKChaE) 2 -NH 2 Lysine residues 3C [153] Ac-E 4 (ChaKChaE) 2 -NH 2 Glutamic acid residues 3C [153] Ac-E(CH 2 CHO)EEEAAAVVVK(C 16 )-NH 2 Silver nanoparticles 3C [154] Fmoc-FFECG Silver nanoparticles 3C [155] C 16 -V 3 A 3 K 4 -NH 2 Folate 3D [156] CKKAAVVK-C 12 KLVWLPK-NH2 3D [157] FFERGD 10-hydroxycamptothecin (HCPT)/cisplatin 3D [158] (VPGVG) 80 (VPGSG) 60 EgA1 3D [159] Nap-G D F D F Phosphate/YSV 3D [160] PhAc-FFAG LDD 3D [16] LVFFGFLG RGD/camptothecin 3D [161] Ac-IHIHIQI-NH 2 Histidine residues 3E [162][163][164] Ac-IHIHIYI-NH 2 Histidine residues 3E [163] Im-KLVFFAL-NH 2 Lysine residues/imidazole groups 3E [165] Ac-KLVFFAL-NH 2 Lysine residues 3E [166] Sialic acid 3F [167,168] AQZ/near-infrared quantum dots/Alexa Fluor 633 3F [169] Ac-HLVFFAL-NH 2 Histidine residues/hemin 3E [170] VK2H (HSG(VK) 4 V D PPT(KV) 4 -NH 2 ) Histidine residues 3E [171] Phenylalanine Zn 2+ 3E [172] 1,4,5,8-naphthalenetetracarboxylic acid diimide Proline residues 3E [173] PFE-C 12 Proline residues 3E [174] PEF-C 12 Proline residues 3E [174] PAEPKI-C 16 Proline residues 3E [175] C 10 -FFVK Lysine residues/Fmoc-Tyrosine 3E [176] Ac-LHLHLQL-NH 2 Histidine residues/hemin 3E [177] Ac-LHLHLFL-NH 2 Histidine residues/hemin 3E [177] Ac-LILHLFL-NH 2 Histidine residues/hemin 3E [177] HN-D PL-CONH-C 16 D-proline/leucine residues/IrCp* 3E [178] KKAAVV(K)-C 12 RTL (RTLAFVRFK) 3F [179] SFEEA...…”
Section: Assembly Motif Display Motif Section Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ac-K 4 (ChaKChaE) 2 -NH 2 Lysine residues 3C [153] Ac-K 2 (ChaKChaE) 2 -NH 2 Lysine residues 3C [153] Ac-E 4 (ChaKChaE) 2 -NH 2 Glutamic acid residues 3C [153] Ac-E(CH 2 CHO)EEEAAAVVVK(C 16 )-NH 2 Silver nanoparticles 3C [154] Fmoc-FFECG Silver nanoparticles 3C [155] C 16 -V 3 A 3 K 4 -NH 2 Folate 3D [156] CKKAAVVK-C 12 KLVWLPK-NH2 3D [157] FFERGD 10-hydroxycamptothecin (HCPT)/cisplatin 3D [158] (VPGVG) 80 (VPGSG) 60 EgA1 3D [159] Nap-G D F D F Phosphate/YSV 3D [160] PhAc-FFAG LDD 3D [16] LVFFGFLG RGD/camptothecin 3D [161] Ac-IHIHIQI-NH 2 Histidine residues 3E [162][163][164] Ac-IHIHIYI-NH 2 Histidine residues 3E [163] Im-KLVFFAL-NH 2 Lysine residues/imidazole groups 3E [165] Ac-KLVFFAL-NH 2 Lysine residues 3E [166] Sialic acid 3F [167,168] AQZ/near-infrared quantum dots/Alexa Fluor 633 3F [169] Ac-HLVFFAL-NH 2 Histidine residues/hemin 3E [170] VK2H (HSG(VK) 4 V D PPT(KV) 4 -NH 2 ) Histidine residues 3E [171] Phenylalanine Zn 2+ 3E [172] 1,4,5,8-naphthalenetetracarboxylic acid diimide Proline residues 3E [173] PFE-C 12 Proline residues 3E [174] PEF-C 12 Proline residues 3E [174] PAEPKI-C 16 Proline residues 3E [175] C 10 -FFVK Lysine residues/Fmoc-Tyrosine 3E [176] Ac-LHLHLQL-NH 2 Histidine residues/hemin 3E [177] Ac-LHLHLFL-NH 2 Histidine residues/hemin 3E [177] Ac-LILHLFL-NH 2 Histidine residues/hemin 3E [177] HN-D PL-CONH-C 16 D-proline/leucine residues/IrCp* 3E [178] KKAAVV(K)-C 12 RTL (RTLAFVRFK) 3F [179] SFEEA...…”
Section: Assembly Motif Display Motif Section Referencesmentioning
confidence: 99%
“…Korendovych and coworkers screened their existing library of β-sheet-forming amphipathic heptamers for hemin coordination and found that nanofibers of the sequence Ac-LHLHLQL-NH 2 successfully bound hemin. [177] They replaced the Gln residue with Phe to increase the…”
Section: Cyclopropanationmentioning
confidence: 99%
“…Allp eptides formed self-assembled structures in the presence of hemin in a1:10 co-factor:peptide ratio to ensure full co-factor binding. [4] Remarkably,n early all peptide-hemin assemblies promoted oxidation, in some cases with high efficiency when compared to hemin alone (Figure S1, Supporting Information and Table 1). Interestingly,a ssemblies formed by LMLHLFL-hemin had the highest peroxidase activity,yet this catalystgave only moderate yields in carbene transfer.…”
mentioning
confidence: 96%
“…[3] Recently,w eh ave demonstrated that assemblies formed by de novo designed peptides bind heme to promote cyclopropanation efficiently and in an enantioselective manner. [4] This reaction requires productivea ssociation of the catalyst with multiple substrates and catalytic turnover withoutt he loss of heme in af lat and fairly featureless system.H ere, we set out to explore the potentialo fh eme-peptide assemblies forp romoting peroxidase-type activity.N atural peroxidases that utilize high valent iron species represent av ery commonc lass of enzymes capable of extremely versatile reactivity,i ncluding polymerization,h ydroxylation and N, and O-dealkylations, among many others. [5] In addition to the practical utility of peroxidases, ranging from waste water purification to polymer productionand biotechnology,peroxidase activity has been extensively studied, providing many benchmarks in both enzymatic and model systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation